Características procedimentais de adultos e idosos que atingiram nível de desenvolvimento operatório formal em provas da escala de desenvolvimento do pensamento lógico (EDPL) e no jogo Quarto - Lemos, Milena Fiorim de Lima (2015)
This thesis aimed to describe features of the formal operational stage in two groups of subjects, that is, adults and the elders, from their performances in EDPL (Logical Thought Development Scale) of Longeot and the game Quarto. We verified specifically: the performance of adults and elders in the trials of EDPL and performance of adults and elders in the game Quarto. In addition, we characterized performance differences between the groups in EDPL and in the game Quarto. In our study we had 12 participants, men, divided into 2 groups, that is, adults aged between 30 and 35 years and elders aged between 60 and 65 years, all university graduates and belonging to at least C social class or higher. The composition of the sample was non-probabilistic and set for convenience. In the analysis of EDPL, instructions allowed us to identify a total score and level (or stage) of development of each participant. Using the game Quarto, we generated 54 matches and a total of 481 moves. This along with previous studies, allowed us to develop a proposal for Heuristic Analysis Levels of the Quarto game. The thesis was divided into three studies. Thus, in the first study, we did a review of foreign papers indexed in Capes Portal that addressed the formal operational stage proposed by Piaget. In the second, we detail the use of EDPL and the results found among the subjects studied. The results showed no significant difference in the manifestation of the structure of formal operational thinking between the groups, but interference of the contents in the resolution of proposed problems especially among the elderly. Thus, we question the exclusive use of EDPL for evaluation of psychological subjects in the circumstances in which they will be classified in one of the stages of development. In the third study, we treat, specifically, the results found with the application of the game Quarto. On these results we found no qualitative differences between adults and elders considering the instrument used and the characteristics that the participants had; the game understanding by the participants was better than the performance observed during the matches; and finally, despite the cognitive capabilities presented in the formal operatory stage, none of the participants could achieve the higher levels of analysis of the game Quarto. In conclusion, we reaffirm, as expected, that structurally adults and the elders are the same as they were all in the formal operatory stage. Moreover, contrary to the initial idea neither were observed procedural differences between our subjects, whereas, obviously, we considered the specificity of the problems presented thereto, as well as the features of the subject.